Cameras replace human observers in multi‐species aerial counts in Murchison Falls, Uganda. Issue 4 (15th March 2020) - Lamprey, Richard; Ochanda, David; Brett, Rob; Tumwesigye, Charles; Douglas‐Hamilton, Iain
Abstract: Wildlife counts in Africa and elsewhere are often implemented using light aircraft with 'rear‐seat‐observer' (RSO) counting crews. Previous research has indicated that RSOs often fail to detect animals, and that population estimates are therefore biased. We conducted aerial wildlife surveys in Murchison Falls Protected Area, Uganda, in which we replaced RSOs with high‐definition 'oblique camera count' (OCC) systems. The survey area comprises forests, woodlands and grasslands. Four counts were conducted in 2015–2016 using a systematic‐reconnaissance‐flight (SRF) strip‐transect design. Camera inclination angles, focal lengths, altitude and frame interval were calibrated to provide imaged strips of known sample size on the left and right sides of the aircraft. Using digital cameras, 24 000 high‐definition images were acquired for each count, which were visually interpreted by four airphoto interpreters. We used the standard Jolly II SRF analysis to derive population estimates. Our OCC estimates of the antelopes – hartebeest, Uganda kob, waterbuck and oribi – were, respectively, 25%, 103%, 97% and 2100% higher than in the most recent RSO count conducted in 2014. The OCC surveys doubled the 2014 RSO estimate of 58 000 Uganda kob to over 118 000. Population size estimates of elephants and giraffes did not differ significantly. Although all four OCC buffalo estimates were higher than the RSO estimates – in one count by 60% – these differences were not significant due to the clumped distribution and high variation in herd sizes, resulting in imprecise estimation by sampling. We conclude that RSO wildlife counts in Murchison have been effective in enumerating elephants and giraffe, but that many smaller species have not been well detected. We emphasize the importance of 60 years of RSO‐based surveys across Africa, but suggest that new imaging technologies are embraced to improve accuracy. Abstract : We conducted four aerial surveys in Murchison Falls, Uganda, where we replace human 'rear‐seat‐observers' (RSOs) with high‐resolution camera systems. The results indicate that the populations of many large mammal species are far higher than previously estimated by RSO‐based counts. We emphasize the importance of 60 years of RSO‐based surveys across Africa, but suggest that new imaging technologies are embraced to improve accuracy.